Analyze the characteristics of electro-hydraulic servo system's position-pressure master-slave control. (June 2018) - Han, Heyong; Liu, Yuan; Ma, Lifeng; Liu, Zhiqi; Quan, Long
For electro-hydraulic system of large flow and overloading, established position and pressure closed-loop control in accordance with the conventional hydraulic servo system theory that system control algorithm is complicated and difficult to implement. This article presents a method which gives priority to position closed-loop control and establishes the corresponding relation between pressure of hydraulic cylinder and load by collecting the pressure signal from rear cavity and rod cavity of hydraulic cylinder; meanwhile, applied position-pressure conversion formula will turn dynamic pressure signal into position signal and compensate the transformed position signal to the master position closed loop of the electro-hydraulic servo system which could achieve the position-pressure master-slave control. The simulation results show that the control method is correct, effective, and feasible. The results indicate that the method can achieve online converting between position and pressure which are different variables and improve the response speed and control precision of the system.